Epidendrum sotoanum - Karremans Lok, Adam Philip (2010)
This volume includes 30 new species from Peru, Colombia, Ecuador, Venezuela, Brazil, and French Guyana, 2 new combinations and status, and many lectotipifications and neotypes. All 100 species are illustrated with botanical illustrations. Each species is illustrated with a black and white analytical illustration showing the floral and vegetative morphology, and includes detailed description in Spanish, with a reduced description in English. Distribution, habitat and recognition of the species are also given.